The Relevance of Character Education in Tafsir Al-Azhar to Education in Indonesia - Akwam, Akwam; Mukhtar, Aflatun; Oviyanti, Fitri (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to analyze Buya Hamka's character education in Tafsir Al Azhar and the relevance of Buya Hamka's character education concept through Tafsir Al Azhar on character education in Indonesia. This research uses a qualitative approach. The research method applied is the Maudhu'i (Thematic) interpretation method. This research data is divided into two sources, namely primary and secondary sources. Primary and secondary data were collected from Al-Azhar tafsir, books, and articles relevant to Buya Hamka's education, focusing on character education. Data in library studies can be collected and managed in editing, organizing, and resulting ways. The next step is data analysis if all the data has been collected. Researchers used several methods to analyze data in this study: reduction, data display, verification, and conclusion drawing. The relevance of Buya Hamka's character education concept in tafsir Al Azhar is related to: a) strengthening the Religious Moderation Ecosystem such as tawassuth (simplicity), tidal (justice), tawazun (balance), and tasamuh (tolerance); b) strengthening MBKM (Blended Learning) which includes a graduate profile with characteristics such as spiritual integrity, insight into diversity, independence, cooperation, critical thinking, and creativity; c) strengthening SCL (Student Centered Learning) which is active in building independent knowledge, attitudes, and behavior; d) Pancasila Youth Profile.